Determinant Atribute Ship Assistance Program Successfulness on Fishermen Welfare Enhancement - Mira Mira (Jurnal Penelitian Kesejahteraan Sosial, 2015)
The purpose of this study is to analyze determinant attribute of the success of ship assistance program to enhance fishermen welfare. The study uses multidimensional scalling (MDS) for economic, social, and institutional dimension. The results of the analysis indicate that stress values for all dimensions is close to 0, it means that configuration measurementattribute for the sustainability of the program in one point is quite appropriate. In social dimension, the attributes that affect the sustainability of the assistance program are an increase community participation in program, increase cooperation in fishing effort, an increase in the number of villages that received the program, and strengthening the involvement of indigenous peoples in the program. In institutional dimension, priorities for improving the sustainability of the program are to strengthen the microfinance institutions, social institutions, and the strengthening of the fishermen group. In the economic dimension, the attributes that affect the sustainability of the program are alternative livelihoods, business profits of the fishery, the fisheries subsidies, availability of human resources (fishermen), and transfer of profits